Eukaryotic Expression System Pichia pastoris Affects the Lipase Catalytic Properties: A Monolayer Study - Bou Ali, Madiha (Public Library of Science, 2014)
Recombinant DNA methods are being widely used to express proteins in both prokaryotic and eukaryotic cells for both fundamental and applied research purposes. Expressed protein must be well characterized to be sure that it retains the same properties as the native one, especially when expressed protein will be used in the pharmaceutical field. In this aim, interfacial and kinetic properties of native, untagged recombinant and tagged recombinant forms of a pancreatic lipase were compared using the monomolecular film technique. Turkey pancreatic lipase (TPL) was chosen as model. A kinetic study on the dependence of the stereoselectivity of these three forms on the surface pressure was performed using three dicaprin isomers spread in the form of monomolecular films at the air-water interface. The heterologous expression and the N-His-tag extension were found to modify the pressure preference and decrease the catalytic hydrolysis rate of three dicaprin isomers. Besides, the heterologous expression was found to change the TPL regioselectivity without affecting its stereospecificity contrary to the N-tag extension which retained that regioselectivity and changed the stereospecificity at high surface pressures. The study of parameters, termed Recombinant expression Effects on Catalysis (REC), N-Tag Effects on Catalysis (TEC), and N-Tag and Recombinant expression Effects on Catalysis (TREC) showed that the heterologous expression effects on the catalytic properties of the TPL were more deleterious than the presence of an N-terminal tag extension.